PENGEMBANGAN KAMUS KOMPETENSI KESELAMATAN KERJA DI PT XYZ INDONESIA TBK - Yudhie Dwi Kristanto; Idqan Fahmi; Agus Maulana (School of Business, Bogor Agricultural University (SB-IPB), 2017)
The occupational health and safety known as K3 (Keselamatan dan kesehatan kerja) is one of the main objectives of PT XYZ Indonesia ltd. operation. Currently PT XYZ Indonesia ltd has possessed an occupational safety competent model for the operational area originally from XYZ global. The objectives of the research are to define the role of the Occupational safety and health (OSH) department, arrange an appropriate competent model and specify the competent level requirements in each job positions and also formulate a development program for each competency. The research uses DACUM (Developing a Curriculum) modified method and refers to AMA (American Management Association) competent literature. The result of the research shows that there are nine main competencies in the department of occupational safety. The four competencies in occupational safety cover 1) OHS mission implementation & tactical planning, 2) controls hazards & manages risks, 3) result oriented OHS, and 4) mastering complexity & manages incidents. While the other five competencies are related to leadership competent, they are 1) communication, 2) partnering, 3) influencing, 4) building trust & personal accountability, 5) critical & analytical thinking. The content designed for the competent model are 1) the list of nine main required competencies, 2) the definition of each competency, 3) the level of each competency, 4) the development for each level, 5) the need of the competent level for each job positions. Based on the research, it shows that the DACUM modified method is suitable to formulate the competency needed from the unit. Keywords: competent, occupational safety, human resources, DACUM, AMA AbstrakKeselamatan dan kesehatan kerja, atau yang juga dikenal sebagai K3, merupakan salah satu tujuan utama dalam operasi PT XYZ Indonesia tbk. Saat ini PT XYZ Indonesia tbk telah memiliki model kompetensi keselamatan kerja untuk area operasional yang berasal dari XYZ global. Tujuan penelitian ini adalah merumuskan peranan-peranan departemen OHS, menyusun model kompetensi yang sesuai dan menentukan tingkat persyaratan kompetensi di masing-masing jabatan, serta merumuskan program pengembangan di setiap kompetensi. Penelitian ini menggunakan metode modified DACUM (Developing A Curriculum) dan merujuk kepada kamus kompetensi AMA (American Management Association). Hasil penelitian menunjukkan ada sembilan kompetensi utama untuk departemen keselamatan kerja. Empat dari sembilan kompetensi tersebut adalah kompetensi keselamatan kerja, yang meliputi 1) OHS mission implementation & tactical planning, 2) controls hazards & manages risks, 3) result oriented OHS, dan 4) mastering complexity & manages incidents. Sebaliknya, lima kompetensi lainnya merupakan kompetensi leadership, yang meliputi 1) communication, 2) partnering, 3) influencing, 4) building trust & personal accountability, 5) critical & analytical thinking. Isi dari model kompetensi yang dibuat adalah 1) daftar sembilan kompetensi utama yang dipersyaratkan, 2) definisi masing-masing kompetensi, 3) tingkatan masing-masing kompetensi, 4) pengembangan untuk setiap tingkatan, 5) kebutuhan tingkat kompetensi untuk setiap posisi jabatan. Dari penelitian juga terlihat bahwa metode modified DACUM dapat dipergunakan untuk merumuskan kompetensi yang dibutuhkan dari unit kerja ini.Kata kunci: kompetensi, keselamatan kerja, sumber daya manusia, DACUM, AMA